CHARACTERISTICS OF EMOTIONAL INTELLIGENCE IN MANAGERS - Sharafitdinov Abdulla XXX; Soyimnazarov Navro‘zbek Baxtiyor ugli; Nishonov Muhammadali Narimon ugli (Journal Park Publishing, 2022)
This article provides feedback on the assessment of leadership style, describes the specific characteristics of emotional intelligence in a manager and various ways and methods of its analysis. It has been shown that emotional intelligence is one of the skills any effective leader needs and that these skills can be learned and strengthened at both the individual and team level.
Keywords: Emotion, creating resonance, neural basis of leadership, real self, ideal self, emotional stability.